Biological responses to silicon and nitrogen-rich PVD silicon nitride coatings. (March 2021) - Marin, E.; Boschetto, F.; Zanocco, M.; Zhu, W.; Adachi, T.; Kanamura, N.; Yamamoto, T.; McEntire, B.J.; Jones, E.N.; Powell, C.; Hendry, J.; Bock, R.M.; et al.
Abstract: Most structural bioceramics are comprised of metallic oxides such as alumina and zirconia. They are generally considered to be completely bioinert, but a non-oxide ceramic, silicon nitride, achieves equivalent levels of mechanical reliability while being bioactive. Silicon nitride can not only stimulate cellular proliferation but it is also antipathogenic with demonstrated efficacy against Gram-positive and Gram-negative bacteria, fungi, and viruses. In this work, three physical vapor deposition coatings with different Si:N ratios (silicon-rich, stoichiometric, and nitrogen-rich) were deposited on mirror-polished silica glass substrates. The coatings were characterized by spectroscopic and microscopic techniques and tested in vitro against E. coli and KUSA-A1 mesenchymal cells. Results showed that nitrogen-enriched Six Ny has a strong antibacterial effect against E. coli and contributes to cellular proliferation while silicon-enriched Six Ny stimulates the production of bone tissue, with higher indexes for mineralization and quality. These results suggest that Six Ny 's biological properties can be optimized for specific applications by carefully tuning its surface chemistry. Highlights: PVD coatings of Si3 N4 with different Si/N ratios could be deposited on silica glass. The N-rich PVD coating showed to improve cellular proliferation and antibacterial effects. The Si-rich PVD coating showed higher amounts of bone tissue formed after KUSA-A1 mesenchymal cell treatment. The stoichiometric coating showed an intermediate behavior.